ANALISIS KEPATUHAN PEMERINTAH INDONESIA TERHADAP KERANGKA KERJASAMA LOMBOK TREATY DALAM PENANGANAN PENYELUNDUPAN IMIGRAN DI WILAYAH INDONESIA - Sri Haryantari, Rachti Noviayu; Wahyudi, Fendy Eko (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
The problem of migrant smuggling is a cross-border issue of concern to the Government ofIndonesia. Since 2006, the framework of Lombok Treaty cooperation has been agreed bythe Government of Indonesia and the Government of Australia to minimize the problem,but in fact the problem of migrant smuggling still occured in the Indonesian territory from2008 to 2013. This research aims to analyze the compliance of the Government ofIndonesia on the framework of lombok cooperation treaty in handling the migrantsmuggling in Indonesian territory. This research uses descriptive-analysis research. Tosharpen the analysis of researcher on the formulation of existing problems, in this study,researcher use the theory of compliance according to Ronald B. Mitchell (2007). Theresults of this study indicate that the Government of Indonesia in this study can becategorized comply on the cooperation of Lombok Treaty in handling the migrantsmuggling in Indonesian territory. The results are based on the adoption by theGovernment of Indonesia on internal requirements, the behavior of the Indonesiangovernment in a better context in the Lombok Treaty, and there is still something to bedone in Indonesia.